Vibration Analysis of Rotating Low Aspect Ratio Blades Idealized as Pretwisted Cantilever Plates - Rawtani, Sunder (My University, 1970)
A method based on the finite element technique is developed for the vibration analysis of rotating and non rotating low aspect ratio turbo machinery blades. The blade is treated as an assembly of flat triangular elements. A partially conforming displacement function is used to obtain the bending stiffness matrix for an element. The accuracy of the method is tested by solving several plate and shell problems for which analytical or experimental results are available. The effect of pre twist, speed oration, disc radius and setting angle on the natural frequencies and the mode shapes is studied; by idealizing the blade as a pre twisted cantilever plate. An extensive review of different methods available for the vibration analysis of blades is also included.
Title: Vibration Analysis of Rotating Low Aspect Ratio Blades Idealized as Pretwisted Cantilever Plates, Author: Sunder Rawtani, Location: Thode